2013
DOI: 10.14233/ajchem.2013.12409
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Antimicrobial and Antioxidant Activities of Artemisia deserti Kracsh Essential Oil from Iran

Abstract: The genus Artemisia (Compositae) contains small herbs or shrubs found in northern temperate regions. Thirty-four species of the genus Artemisia are found in Iran, of which two are endemic viz., A. melanolepis Boiss. and A. kermanensis Podl. 1. Several Artemisia species have medicinal importance and are useful in traditional medicine for the treatment of a variety of diseases and complaints. A. annua is a traditional medicinal herb of China. It is presently being cultivated on a commercial scale in China and Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…The MBIC and MBEC results revealed that the MBIC values for the tested bacteria ranged from 6.25 to 100 µL/mL, whereas the MBEC values ranged from 12.5 to 200 µL/mL (Table 4). Our findings for ArJ essential oil antimicrobial activity are consistent with previously published data [17,24,[82][83][84][85]. Benmansour et al demonstrated that ArJ essential oil had an excellent inhibitory effect against tested MRSA (methicillin-resistant Staphylococcus aureus), S. aureus, and B. subtilis [17], which is consistent with our results.…”
Section: Minimum Inhibitory Concentration (Mic) Minimum Biocidal Conc...supporting
confidence: 93%
“…The MBIC and MBEC results revealed that the MBIC values for the tested bacteria ranged from 6.25 to 100 µL/mL, whereas the MBEC values ranged from 12.5 to 200 µL/mL (Table 4). Our findings for ArJ essential oil antimicrobial activity are consistent with previously published data [17,24,[82][83][84][85]. Benmansour et al demonstrated that ArJ essential oil had an excellent inhibitory effect against tested MRSA (methicillin-resistant Staphylococcus aureus), S. aureus, and B. subtilis [17], which is consistent with our results.…”
Section: Minimum Inhibitory Concentration (Mic) Minimum Biocidal Conc...supporting
confidence: 93%
“…AV is one of the famous Artemisia species compared to others such as A. absinthium , A. nilagirica , and A. deserti , (Kazemi et al, 2013; Pelkonen et al, 2013; Sati et al, 2013). AV-EOs have a high content of eucalyptol and Cis-β-Terpineol, which shown anti-inflammatory and antioxidant effects against various diseases, including respiratory disease, pancreatitis, colon damage, and non-alcoholic steatohepatitis (Murata et al, 2015; Seol and Kim, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ali et al [ 111 ] reported that 0.005 mg/mL of ethyl acetate fraction of A. macrocephala oil showed 121.5% radicle scavenging activity. However, essential oil of A. deserti exhibited more antioxidant activity by DPPH free radical scavenging method (57.2%) than that of β-carotene bleaching test (50%) [ 17 ]. In the β-carotene method, A. dracunculus oil also showed 50% scavenging activity [ 21 ].…”
Section: Antioxidant Activitymentioning
confidence: 99%